Relative Managerial Networking and Performance: The Moderating Role of Environmental Context. (8th March 2020) - Rho, Eunju; Han, Sumin
Abstract: This article examines how a dynamic view of managerial networking contributes to the cumulative knowledge of the study of managerial networking in the public sector . The current study contributes to our understanding of the relative influences of past and current networking relationships on current program performance by (1) exploring the nonlinear effects of relative levels of networking on performance and (2) investigating how relative networking influences may interact with organizational conditions characterized by different aspects of institutional and task environments . Employing a panel data set of U . S . local school districts from 1999 to 2015, the research finds that organizational performance improves at an increasing rate as the relative level of managerial networking increases and that the advantages of relative networking are leveraged more effectively when the organization meets its institutional requirements and when the environment is less complex, highly munificent, and highly turbulent .